Deep Extragalactic VIsible Legacy Survey (DEVILS): consistent multiwavelength photometry for the DEVILS regions (COSMOS, XMMLSS, and ECDFS). Issue 1 (5th June 2021) - Davies, L J M; Thorne, J E; Robotham, A S G; Bellstedt, S; Driver, S P; Adams, N J; Bilicki, M; Bowler, R A A; Bravo, M; Cortese, L; Foster, C; Grootes, M W; et al.
ABSTRACT: The Deep Extragalactic VIsible Legacy Survey (DEVILS) is an ongoing high-completeness, deep spectroscopic survey of ∼60 000 galaxies to Y < 21.2 mag, over ∼6 deg 2 in three well-studied deep extragalactic fields: D10 (COSMOS), D02 (XMMLSS), and D03 (ECDFS). Numerous DEVILS projects all require consistent, uniformly derived and state-of-the-art photometric data with which to measure galaxy properties. Existing photometric catalogues in these regions either use varied photometric measurement techniques for different facilities/wavelengths leading to inconsistencies, older imaging data and/or rely on source detection and photometry techniques with known problems. Here, we use the ProFound image analysis package and state-of-the-art imaging data sets (including Subaru-HSC, VST-VOICE, VISTA-VIDEO, and UltraVISTA-DR4) to derive matched-source photometry in 22 bands from the FUV to 500 μ m. This photometry is found to be consistent, or better, in colour analysis to previous approaches using fixed-size apertures (which are specifically tuned to derive colours), but produces superior total source photometry, essential for the derivation of stellar masses, star formation rates, star formation histories, etc. Our photometric catalogue is described in detail and, after internal DEVILS team projects, will be publicly released for use by the broader scientific community.